Academic self-efficacy and its relation to the barriers to seeking help for mental health problems in University Students of Lima - Palacios Jimenez, Alberto Salvador (2018)
Objectives: To determine the relationship between academic self-efficacy and the barriers to seeking help for mental health problems in students of a public university in Lima. Materials and methods: The present is a quantitative, not experimental, cross-sectional study. The sample consisted of 131 students from a public university of Lima. The instruments used were the Scale of perceived self-efficacy in academic situations and the Barriers Questionnaire for seeking help for mental health problems. Results: Regarding Academic Self-efficacy, 40 students (30.53%) presented a high level of self-efficacy, 67 (51.15%) obtained a regular level and 24 (18.32%) obtained a low level. With respect to barriers to seeking help for mental health problems, 67 students (51.15%) had a high presence of barriers, 31 (23.66%) had a regular presence of barriers and 33 (25.19). %) obtained a low presence of barriers. Conclusions: There is a significant, moderate, inversely proportional relationship between academic self-efficacy and barriers to seeking help for mental health problems in a group of students at a public university in Lima.